Does knee extensor torque determine performance in the step-down test in women with PFP? - Brollo, Raphaella Suenson Beato [UNESP]; Araujo, Isabela Vitoria Souza [UNESP]; Spinoso, Deborah Hebling [UNESP] (Elsevier, 2025)
Background Patellofemoral pain (PFP) is characterized by pain around the patella or in the anterior region, occurring mainly during activities that increase overload on this joint. Its incidence is higher in women, with high rates of recurrent pain and decreased functionality. Objectives To investigate the association between knee extensor torque and performance in the step descent test in women with PFP. Methods The project was approved by the Ethics Committee (5.690.291). Initially, anamnesis was performed to obtain personal data. To assess function, the step-down test was performed, in which participants stood on a 20 cm high step with their feet supported and their hands on their pelvic girdle. The participant was asked to touch the ground with the heel of the unaffected leg and return to the starting position. The participant was asked to perform as many repetitions as possible in 30 seconds. To assess knee extensor joint torque, the Biodex® isokinetic dynamometer was used. Initially, there was a 5-minute warm-up on the treadmill and the volunteers were positioned with their hips and knees flexed at 90°. Torque was assessed at an angle of 90 to 30 degrees of flexion, at a speed of 60°/second. The protocol consisted of 3 maximum concentric contractions. For statistical analysis, Pearson's correlation test was used, with a significance level of p < 0.05. Results Performance in the step descent test is positively associated with maximum concentric knee extension torque (r = 0.351, p = 0.006) in women with PFP. Conclusion The decreased ability to produce knee extensor force negatively affects the functional performance of women with PFP. Implications Women with PFP have impaired ability to produce maximum knee extension force and this interferes with their functional performance. Understanding the factors that involve limitations in the functional performance of women with PFP can help in clinical practice, guiding treatment programs and making prognosis more accurate. Functional tests are low-cost and simple to perform, which can be used to monitor the progress of people with PFP and their response to resistance training, especially of the knee extensors.